Agro-Climatic Factors and Their Influence on Sustainable Soybean Production - Rahma Harti, Adi Oksifa; Sakhidin, Sakhidin; Muhammad Rif'an; Totok Agung (Green Publisher, 2024)
This research explores the impact of intercropping corn and soybean, along with the combined effects of Azolla pinnata dose, the best soybean variety, and cytokinin concentration, on enhancing the physiology and agronomy of the plants. The study was conducted using 36 experimental units in a plot between soybean and corn. Various parameters were observed, including seed viability and vigor, soil analysis, nutrient content analysis of POC Azolla pinnata, temperature, air humidity, sunlight radiation, rainfall, pest infestation, diseases, and weeds. Additionally, plant height, leaf count, secondary branch count, total plant dry weight, leaf chlorophyll, leaf area ratio, leaf chlorophyll index, and stomatal conductance were measured. The data were analyzed using Djajasukanta and Sitompul-Guritno calculations, focusing on the average relative growth rate (RGR), average net assimilation rate (NAR), and root-shoot ratio (RSR). The results demonstrated that intercropping corn and soybean with the combination of Azolla pinnata dose, the best soybean variety, and cytokinin concentration had a positive impact on soybean production and quality. The Anjasmoro variety showed favorable outcomes in various parameters, such as plant height, leaf count, and branch count. Physiological leaf analysis revealed that the treatment combination with the Anjasmoro variety exhibited optimal photosynthetic rates and chlorophyll content, indicating higher photosynthesis efficiency. Moreover, the treatment with the Dega 1 variety displayed faster growth and efficient resource allocation, as evident from the high RSR value. The selection of the best soybean variety, Azolla pinnata dose, and cytokinin concentration can lead to sustainable improvements in soybean crop yield. These findings hold significant implications for agricultural management and enhancing food security.